Waste-to-energy and electricity generation: Analysis for Saudi Arabia - Alajmi, Reema Ghazi (Journal of Economic, Administrative and Legal Sciences, 2022)
Saudi Arabia is a developing country experiencing both rapid economic growth and vast urbanization. These have led to waste disposal problems. Therefore, waste-to-energy (WTE) processes, a source of renewable energy, are expected to play an increasingly important role in sustainable management of municipal solid waste (MSW). The purpose of this paper is to estimate the energy produced from the WTE method, to assist policymakers to develop a strategy that enhances the environmental quality, through reducing energy generation in the electricity sector. This study begins by presenting Saudi’s current MSW management situation and its waste disposal process as well as the major challenges associated with Saudi’s WTE incineration before discussing the economic and environmental benefits of the WTE method. Since waste can be used to produce energy for electricity and heat, this study estimated energy generated from WTE technology through employing estimated baseline scenario and future scenarios. Findings indicated that future scenarios are better than the business-as-usual scenario. The paper concludes that the WTE method can produce energy for electricity generation which in turn reduces the volume and the production of greenhouse gas (GHG) emissions produced from MSW. The waste-to energy approach with supportive policies could lead the country to achieve sustainable development.